Whole-transcriptome microarray analysis reveals regulation of Rab4 by RBM5 in neurons. (11th October 2017) - Jackson, Travis C.; Kotermanski, Shawn E.; Kochanek, Patrick M.
Graphical abstract: Highlights: Rab4 levels are increased in RBM5 knockdown neurons vs. controls. Oligomeric SERT levels are decreased in RBM5 knockdown neurons vs. controls. Monomeric SERT uptake/endocytosis is increased in RBM5 knockdown neurons vs. controls. RBM5 is a novel regulator of Rab4 signaling in neurons. Abstract: RNA binding motif 5 (RBM5) is a nuclear protein that modulates gene transcription and mRNA splicing in cancer cells. The brain is among the highest RBM5-expressing organ in the body but its mRNA target(s) or functions in the CNS have not been elucidated. Here we knocked down (KO) RBM5 in primary rat cortical neurons and analyzed total RNA extracts by gene microarray vs. neurons transduced with lentivirus to deliver control (non-targeting) shRNA. The mRNA levels of Sec23A (involved in ER-Golgi transport) and the small GTPase Rab4a (involved in endocytosis/protein trafficking) were increased in RBM5 KO neurons relative to controls. At the protein level, only Rab4a was significantly increased in RBM5 KO extracts. Also, elevated Rab4a levels in KO neurons were associated with decreased membrane levels of oligomeric serotonin transporters (SERT). Finally, RBM5 KO was associated with increased uptake of membrane-derived monomeric SERT. Significance: Rab4a is involved in the regulation of endocytosis and protein trafficking in cells. In the CNS it regulates diverse neurobiological functions including (but not limited to) trafficking of transmembrane proteins involved in neurotransmission (e.g. SERT), maintaining dendritic spine size, promoting axonal growth, and modulating cognition. Our findings suggest that RBM5 regulates Rab4a in rat neurons.